Pembrolizumab Induced Calcitriol-Mediated Hypercalcemia. (6th January 2023) - Oommen, Tiffany T.; Sun, Kelly; Barranco-Trabi, Javier; Berenberg, Jeffrey; Kim, Myungjin
Abstract : PD-1/PD-L1 inhibitors such as pembrolizumab have radically improved the prognosis for many patients with advanced malignancies. Although revolutionary, its use can be complicated and limited by various immune-related adverse effects. Effective management depends on early recognition and prompt intervention. Herein, we describe a unique syndrome of hypercalcemia, with associated acute renal injury and hypoxic respiratory failure that was responsive to corticosteroids suggestive of immunotoxicity from pembrolizumab.